Optimal planning target margin for prostate radiotherapy based on interfractional and intrafractional variability assessment during 1.5T MRI-guided radiotherapy - Kim, Jina; Sung, Jiwon; Lee, Seo Jin; Cho, Kang Su; Chung, Byung Ha; Yang, Dongjoon; Kim, Jihun; Kim, Jun Won (Frontiers in Oncology, 2023)
Introduction We analyzed daily pre-treatment- (PRE) and real-time motion monitoring- (MM) MRI scans of patients receiving definitive prostate radiotherapy (RT) with 1.5 T MRI guidance to assess interfractional and intrafractional variability of the prostate and suggest optimal planning target volume (PTV) margin. Materials and Methods Rigid registration between PRE-MRI and planning CT images based on the pelvic bone and prostate anatomy were performed. Interfractional setup margin (SM) and interobserver variability (IO) were assessed by comparing the centroid values of prostate contours delineated on PRE-MRIs. MM-MRIs were used for internal margin (IM) assessment, and PTV margin was calculated using the van Herk formula. Results We delineated 400 prostate contours on PRE-MRI images. SM was 0.57±0.42, 2.45±1.98, and 2.28±2.08 mm in the left-right (LR), anterior-posterior (AP), and superior-inferior (SI) directions, respectively, after bone localization and 0.76±0.57, 1.89±1.60, and 2.02±1.79 mm in the LR, AP, and SI directions, respectively, after prostate localization. IO was 1.06±0.58, 2.32±1.08, and 3.30±1.85 mm in the LR, AP, and SI directions, respectively, after bone localization and 1.11±0.55, 2.13±1.07, and 3.53±1.65 mm in the LR, AP, and SI directions, respectively, after prostate localization. Average IM was 2.12±0.86, 2.24±1.07, and 2.84±0.88 mm in the LR, AP, and SI directions, respectively. Calculated PTV margin was 2.21, 5.16, and 5.40 mm in the LR, AP, and SI directions, respectively. Conclusions Movements in the SI direction were the largest source of variability in definitive prostate RT, and interobserver variability was a non-negligible source of margin. The optimal PTV margin should also consider the internal margin.